Board mechanisms and Malaysian Family Companies' Performance - Noor Afza Amran,; Ayoib Che Ahmad, (FEP, 2011)
Many overseas studies discussed the topic of corporate governance and performance in family companies, however, few studies have been conducted in Malaysia. The objective of this paper is to examine the board mechanisms and family companies’ performance using three performance indicators (Tobin’s Q, Earnings Per Share & Operating Cash Flow). The sample size is 189 family companies listed on Bursa Malaysia from 2003 to 2007. The findings from this study reveal that some of the board mechanisms influence family companies’ performance. This study evidenced that family companies with a large board size, low directors’ expertise and duality leadership contribute to higher family companies’ performance. However, this study found that the academic qualification of directors does not influence firm performance. Therefore, generally, regulators and investors need to be sensitive to the fact that family companies do have differences in corporate governance practices compared to non-family companies.